Effect of Nurse -led lifestyle adaptation training on Emotional Regulation and Resilience among patients with Coronary Artery Disease - M L, Mrs. Sarika; Das, Dr. Sasmita; Behera, Dr. Suresh Kumar (South Eastern European Journal of Public Health, 2024)
Background:Coronary artery disease is asignificantbase of death globally. Patients who have coronary artery disease need to adhere to their new lifestyle practices to reduce mortality and morbidity related to the disease.Resilience and good emotional regulationhelp the patients toadhere to the lifestyle changes and pharmacological therapy. The present study focused on determining the effect of a nurse-led lifestyle adaptation program on improving emotional regulation and resilience. Methodology: This quasi-intervention study was conducted among 69 patients with coronary artery disease in a tertiary care center in Bhubaneswar. The samples were divided into the study and the control group (34 and 35, respectively).After getting consent from the patients, the pre-assessment was done. Then, the intervention group received the nurse-led lifestyle adaptation training for 20-30 minutes, and the post-assessmentwas done after one month and 15 days. Results and discussion:The sampleage in the interventionand control groups was 57.7 ± 6.9 years and 57.1 ± 6.4 years, respectively. The resilience was reported as usualby around 20% of participants in the intervention and control groups. The resilience valuedoes not have much difference in the intervention and control groups. Still, the emotional regulation exhibits a significant difference (P<0.001) from 18.1±4.5 from the pretest to 15.5±4.6 after six weeks. A five-year follow-up study showed a decrease in unfavorable cardiac events among the patients who obtained relaxation therapy and regular cardiac rehabilitation. Conclusion: The nurse-led lifestyle adaptation training effectively improvedemotional regulation among patients with coronary artery conditions.